Predictors of efficacy of viscosupplementation for the treatment of hip osteoarthritis: a retrospective cohort study. Issue 1 (January 2021) - Kim, David Daewhan; Meselhy, Ehab; Sibai, Nabil
Abstract : Background: Hip injections of hyaluronic acid (HA) have been used off-label to treat osteoarthritis (OA). The purpose of this retrospective cohort study of adults with OA was to review predictive factors and duration of action for patients who responded to HA hip injections. Methods: After institutional review board (IRB) approval, patients who had HA hip injections from 2014 to 2018 were retrospectively reviewed. Visual analog scale (VAS) scores obtained 1 mo after three injections were collected. Patients were classified into two groups: positive outcome (50% or greater reduction of VAS) and negative outcome (less than 50% reduction of VAS). Comparison of demographics, functional status, OA severity on Kellgren-Lawrence Grading Scale (KL), previous treatments, type of HA, and procedure techniques were performed. Continuous variables were summarized in mean and standard deviation (SD), and compared using two-sample t -test. Categorical variables were summarized in frequency and proportion, then compared using chi-square test or Fisher exact test. Results: The 157 patients who were reviewed had the following levels of OA severity: 24.3% mild (KL grade II), 25% moderate (KL grade III), 50.7% severe (KL grade IV). Positive outcomes were reported in 29.3% of patients, and 70.7% had "negative" outcomes. The positive outcome group had a mean duration (for 50% or greater decrease of VAS) of 4.24 mo (SD 3.62). The positive outcome group had milder OA (KL grades II to III) ( P <0.001) and younger age ( P =0.03). No difference was noted among the two groups for other variables. Conclusions: Injections of HA for hip OA using the full recommended dosage regimen of commercially available HA products can be beneficial in select patients. The main predictors of significant response were younger age and mild to moderate (KL grade II to III) OA. Level of Evidence: Level III.